Fabrication of Nanosized Reactive Nickel Oxide Composite Particles for Degradation of Textile Dye (Journal of Scientific Research, 2017)
In this research we focused on to develop new nanocomposite materials that have capacity to de-colorize and degrade industrial effluent. At first NiO nanoparticle were synthesized by simple liquid phase process using Ni(NO3)2.6H2O and NH4OH followed by calcinations of the produced Ni(OH)2 as precursor at 400°C. NiO nanoparticles were modified to produce NiO/SiO2 nanocomposite particles. Finally tri-layered inorganic/organic nanocomposite particles were prepared by seeded polymerization of epoxide functional monomer, glycidyl methacrylate (GMA) in presence of NiO/SiO2 nanocomposite seed particles. The composite particles were named as NiO/SiO2/PGMA and the obtained particles were utilized as a photocatalyst for the UV-light assisted degradation of congo red (CR), a model azo dye. Degradation efficiency decreased with the increase of initial CR concentration and a maximum efficiency of 100% was achieved when the CR concentration was 40 mg/L.